Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species - Santos-Silva, Antonio; Galileo, Maria Helena M.; Mcclarin, Jim (Zootaxa, 2018)
Sparna Thomson, 1864 and Carterica Pascoe, 1858 are divided into seven genera: Sparna, Carterica, Francisparna gen. nov., Batesparna gen. nov., Allocarterica gen. nov., Piriana gen. nov., Miguellus gen. nov., and Confluentia gen. nov. From the species currently placed in Sparna, only S. lycoides Thomson, 1864 is maintained in the genus, and only Carterica mucronata (Olivier, 1795) is considered a true Carterica. Sparna bosqi Gilmour, 1954 is revalidated and included in a new genus. The following new species are described: Sparna tavakiliani, from Colombia; Piriana birai, and P. nearnsi, from Brazil (Pará); P. consimilis, from Ecuador; P. svachai, from Brazil (Rio Grande do Sul); Confluentia nigra, from Colombia; and C. flavomaculata, from Peru. Miguellus monnei, sp. nov., gen. nov. is described from Ecuador. Keys to species of Piriana and Confluentia are provided, as well as a key to the genera from the division of Sparna and Carterica, including Miguellus.